Novel carbohydrazones including 5-substituted isatin: Synthesis, characterization, and quantum-chemical studies on the relationship between electronic and antioxidant properties. (May 2020) - Çavuş, M. Serdar; Yakan, Hasan; Muğlu, Halit; Bakır, Temelkan
Abstract: 1-(5-Chloro-2-oxoindolin-3-ylidene)carbohydrazone (1 ), 1-(5-fluoro-2-oxoindolin-3-ylidene)carbohydrazone (2 ), 1-(5-methoxy-2-oxoindolin-3-ylidene)thiocarbohydrazone (3 ), and 1-(5-methoxy-2-oxoindolin-3-ylidene)carbohydrazone (4 ) were synthesized from 5-substituted isatins and thiocarbohydrazide/carbohydrazide under reflux in absolute ethanol. Fourier transform-IR, 1 H NMR, and 13 C NMR spectroscopy and elemental analysis were used to characterize the structures of the compounds. Experimental spectroscopic data were supported by theoretical data obtained with the Becke three-parameter Lee–Yang–Parr (B3LYP) correlation functional with cc-pvtz and 6–311++g(2d, 2p) basis sets. The antioxidant properties of the compounds were examined on the basis of the quantum-chemical calculations. Analysis by quantum theory of atoms in molecules (QTAIM), density of states analysis (DOS), frontier molecular orbital eigenvalues (FMO), and other chemical reactivity descriptors were used to elucidate the relationship between electronic and antioxidant characteristics of the compounds. The in vitro antioxidant activity of all the compounds were evaluated by the 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free-radical scavenging method. Antioxidant activity was in the following order: 3 > 4 > butylated hydroxytoluene (BHT) > 2 > 1 . Theoretical investigations of the structural and antioxidant properties were performed. Graphical abstract: Image 1 Highlights: Some novel carbohydrazones including 5-substituted isatin were synthesized. The structures were elucidated by spectroscopic methods. The antioxidant activity of the synthesized compounds was studied by the DPPH free radical scavenging method. DFT calculations were performed to determine the stable electronic structure and charge density distributions. Investigation the relationship between the electronic properties of atoms in molecules and antioxidant activity.